DETERMINING THE RESERVES FOR REDUCING THE COST OF LIVESTOCK PRODUCTS AND IMPROVING THE QUICK ANALYSIS METHOD - Menglikulov Bakhtiyor Yusupovich (KONFERENSIYALAR, 2025)
The article studies methods for determining and expressanalysis of reserves for reducing the cost of livestock products. A conclusionwas formulated and proposals were made to reduce the cost of livestockproducts and improve the express analysis method.